Apoptosis and Phagocytosis Activity of Macrophages Infected by Mycobacterium tuberculosis Resistant and Sensitive Isoniazid Clinical Isolates - Rachmawaty, Farida J.; Wibawa, Tri; Soesatyo, Marsetyawan H.N.E. (Indonesian Journal of Biotechnology, 2006)
Mycobacterium tuberculosis (M.tb) is the main causative pathogen that cause the pulmonary tuberculosis.Intracellular M.tb was reported able to induce macrophages apoptosis, which may have crucial role in the regulationof immun response against M.tb infection. As an intracellular bacteria, M.tb able to live and replicate withinmacrophages. Phagocytosis is the first step to achieved this condition. The induction of macrophages apoptosis byINH resistant and sensitive M.tb clinical isolates, and H37Rv was studied. The macrophages apoptosis level weremeasured using an Ag-capture ELISA for histone and fragmented DNA (Cell Death Detection ELISAplus, RocheDiagnostic GmBH). Phagocytosis activity also analyzed, after staining using fluorescence dye (AcriFluorTM, ScientificDevice Lab.). The results showed that there was no significantly different between INH resistant and sensitive M.tbclinical isolates in respect their ability to induce apoptosis. The phagocytosis activity among the clinical isolates wasshown to be strain dependent, and undistinguishable between the Mtb clinical isolates. There was no associationbetween macrophages apoptosis level and the phagocytosis activity. These data suggested that among the virulentMtb clinical isolates, the ability to induce macrophages apoptosis and phagocytosis were consistently in comparablelevelKeywords: Mycobacterium tuberculosis, apoptosis, phagocytosis, macrophages, isoniazid